Alzheimer’s Retinopathy: Seeing Disease in the Eyes - Mirzaei, Nazanin; Shi, Haoshen; Oviatt, Mia; Doustar, Jonah; Rentsendorj, Altan; Fuchs, Dieu-Trang; Sheyn, Julia; Black, Keith L.; Koronyo, Yosef; Koronyo-Hamaoui, Maya (Frontiers in Neuroscience, 2020)
The neurosensory retina emerges as a prominent site of Alzheimer’s disease (AD) pathology. As a CNS extension of the brain, the neuro retina is easily accessible for noninvasive, high-resolution imaging. Studies have shown that along with cognitive decline, patients with mild cognitive impairment (MCI) and AD often suffer from visual impairments, abnormal electroretinogram patterns, and circadian rhythm disturbances that could, at least in part, be attributed to retinal damage. Over a decade ago, our group identified the main pathological hallmark of AD, amyloid β-protein (Aβ) plaques, in the retina of patients including early-stage clinical cases. Subsequent histological, biochemical and in vivo retinal imaging studies in animal models and in humans corroborated these findings and further revealed other signs of AD neuropathology in the retina. Among these signs, hyperphosphorylated tau, neuronal degeneration, retinal thinning, vascular abnormalities and gliosis were documented. Further, linear correlations between the severity of retinal and brain Aβ concentrations and plaque pathology were described. More recently, extensive retinal pericyte loss along with vascular platelet-derived growth factor receptor-β deficiency were discovered in postmortem retinas of MCI and AD patients. This progressive loss was closely associated with increased retinal vascular amyloidosis and predicted cerebral amyloid angiopathy scores. The new developments brought excitement to the field of retinal exploration in AD. Indeed, many questions still remain open, such as queries related to the temporal progression of AD-related pathology in the retina compared to the brain, the relations between retinal and cerebral changes and whether retinal signs can predict cognitive decline. The extent to which AD affects the retina, including the susceptibility of certain topographical regions and cell types, are further under intense investigation. Advances in retinal amyloid imaging, hyperspectral imaging, optical coherence tomography, and OCT-angiography encourage the use of such modalities to achieve more accurate, patient- and user-friendly, noninvasive detection and monitoring of AD. In this review, we summarize the current status in the field while addressing the many unknowns regarding Alzheimer’s retinopathy.